1994
DOI: 10.1177/088307389400900411
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term MRI Changes in Brain After Pediatric Open Heart Surgery

Abstract: We performed magnetic resonance imaging (MRI) on the brain and neurologic examinations on 23 children after open heart surgery for congenital heart disease. Twenty children also had psychometric assessments. Examinations were performed at a mean age of 66 months (range, 26 to 180 months). Age at operation was less than 1 month in 43% and more than 6 months in 45%. Abnormal scans were found in 17 (74%) and showed diffuse findings consistent with hypoxic-ischemic encephalopathy, with or without areas of cortical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
1

Year Published

1995
1995
2014
2014

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(28 citation statements)
references
References 15 publications
1
26
0
1
Order By: Relevance
“…16 Clinical and silent cerebral infarction have also been reported in relation to cardiac surgery for congenital heart disease. 17,18 Similar data exist for adults undergoing coronary artery bypass grafting surgery. 19…”
Section: Cardiac Diseasesupporting
confidence: 51%
“…16 Clinical and silent cerebral infarction have also been reported in relation to cardiac surgery for congenital heart disease. 17,18 Similar data exist for adults undergoing coronary artery bypass grafting surgery. 19…”
Section: Cardiac Diseasesupporting
confidence: 51%
“…Various studies have reported that preexisting brain damage may be detected by neuroimaging before operation, and even in those without chromosomal aberrations or multiple minor congenital anomaly syndromes, congenital brain anomalies may be present. [22][23][24][25] Seizures after open-heart surgery are frequent and were recorded in 10% of our population. 26--28 They were not associated with any study variable.…”
Section: Psychometric and Neurologic Examinationsmentioning
confidence: 98%
“…The risk of stroke in children with CHD is related to the underlying abnormality, diagnostic and surgical procedures, and associated genetic or acquired factors that predispose children to thrombosis. Silent infarction may also occur as demonstrated by neuroimaging studies that revealed permanent neurologic damage in infants undergoing cardiac surgery for CHD [18]. A pre-and postoperative magnetic resonance imaging (MRI) study of 24 infants undergoing pediatric surgery revealed that 67% of cases developed new lesions or worsening of preoperative lesions [17].…”
Section: Cardiac Disordersmentioning
confidence: 99%